Redescription of the genus Cheleocloeon Wuillot & Gillies 1993 (Ephemeroptera: Baetidae) with descriptions of three new species from Zambia and Uganda - Kluge, Nikita J. (Zootaxa, 2016)
Revised characteristics of Cheleocloeon Wuillot & Gillies 1993 are given. This taxon occupies a separate position within Anteropatellata. The species described as Cheleocloeon mirandei Lugo-Ortiz & McCafferty 1997 and Cheleocloeon sigiense Gillies 2001, as well as the species originally described as Centroptilum falcatum Crass 1947, do not belong to Cheleocloeon. Three new species, Ch. clavifolium sp. n., Ch. lancetofolium sp. n. and C. truncifolium sp. n. from Zambia and Uganda are described based on larvae, subimagoes, imagoes of both sexes and eggs associated by rearing. Additional characteristics of Ch. yolandae Wuillot 1993, Ch. carinatum Wuillot 1993 and Ch. soldani Gattolliat & Sartori 2008 are given based on new material. Some species of Cheleocloeon without formal names are reported from Zambia and Uganda.